HydrothermalFoam v1.0: a 3-D hydrothermal transport model for natural submarine hydrothermal systems - Z. Guo (Geoscientific Model Development, 2020)
Herein, we introduce HydrothermalFoam, a three-dimensional hydro-thermo-transport model designed to resolve fluid flow within submarine hydrothermal circulation systems. HydrothermalFoam has been developed on the OpenFOAM platform, which is a finite-volume-based C++ toolbox for fluid-dynamic simulations and for developing customized numerical models that provides access to state-of-the-art parallelized solvers and to a wide range of pre- and post-processing tools. We have implemented a porous media Darcy flow model with associated boundary conditions designed to facilitate numerical simulations of submarine hydrothermal systems. The current implementation is valid for single-phase fluid states and uses a pure-water equation of state (IAPWS-97). We here present the model formulation; OpenFOAM implementation details; and a sequence of 1-D, 2-D, and 3-D benchmark tests. The source code repository further includes a number of tutorials that can be used as starting points for building specialized hydrothermal flow models. The model is published under the GNU General Public License v3.0.